Occurrence of Argyrotaenia sphaleropa Meyrick (1909) (Lepidoptera: Tortricidae) in Caesalpinia spinosa (Molina) Kuntze Britton & Rose (1824) - Murga, Hipólito (2015)
Derivatives pods tara (Caesalpinia spinosa (Molina) Kuntze Britton & Rose (1824)), have increasing industrial demands. In October 2015 in the province of San Marcos, Cajamarca region, the occurrence of attack Argyrotaenia aphaleropa Meyrick (1909) was verified tara pods, causing direct damage, interfering in its development and growth, depreciating the product commercially, generating restrictions exports; so this plague its integrated demand to decrease the incidence and prevent the entry to other regions free of attacks handling.